2004
DOI: 10.1177/00343552030470020201
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Instrument to Measure Consumer Satisfaction in Vocational Rehabilitation

Abstract: Although state agencies are required by law to assess their consumers' satisfaction with vocational rehabilitation (VR), each state uses its own instrument to measure satisfaction. This not only makes comparisons across states impossible but also means that the quality of these instruments varies widely from state to state. As with other satisfaction research in general, there have been, and continue to be, many problems with the measurement of consumer satisfaction in VR. The purpose of this study was to crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 21 publications
1
18
0
2
Order By: Relevance
“…The above mentioned Capelia and Turner (2004) propose a scoring method and assessment of customer answers within the interval [2 (absolutely agree); −2 (absolutely disagree)]. This is a simplified assessment of criteria importance by giving them weight from limited selection 2, 1 and 0.…”
Section: Assessment Of Customer Satisfactionmentioning
confidence: 99%
“…The above mentioned Capelia and Turner (2004) propose a scoring method and assessment of customer answers within the interval [2 (absolutely agree); −2 (absolutely disagree)]. This is a simplified assessment of criteria importance by giving them weight from limited selection 2, 1 and 0.…”
Section: Assessment Of Customer Satisfactionmentioning
confidence: 99%
“…Tai vienas iš kriterijų, pagal kurį galima spręsti, kurias veiklas tikslinga plėtoti, kurias tobulinti, kurių atsisakyti. Siekiant įvertinti, kiek patenkina vartotojų poreikius jau teikiamos paslaugos, tikslinga taikyti Capelia ir Turner [27] siūlomą paslaugų įmonių vartotojų tyrimų metodiką. Sudarydamos metodiką, autorės rėmėsi daugelio mokslininkų nuomone ir savo atliktais profesinio orientavimo įstai-gų paslaugų vartotojų pasitenkinimo tyrimais.…”
Section: Rinkos Poreikių įVertinimasunclassified
“…Atsižvelgiant į tai, kad Capelia ir Turner [27] siūloma-me klausimyne didelė dalis kriterijų yra kokybiniai, vertinimo subjektyvumui sumažinti prasminga būtų dalį jų pakeisti kiekybiniais ir nustatyti ribojimą, kad ne mažiau kaip pusė kriterijų būtų kiekybiškai vertinami. Pagal tokios vartotojų apklausos metu gautus atsakymus jų pasitenkinimą teikiamomis paslaugomis galima nustatyti skaičiuojant suvestinę kriterijaus reikšmę…”
Section: Rinkos Poreikių įVertinimasunclassified
“…Although the researcher was not able to identify statistically significant results between informed consumer choice and consumer satisfaction assuming due to the sample of the study, Condeluci (1987), Kieran & Hagner (1995) and Parent (1993) suggested that it was a common belief that the high levels of informed consumer choices led to higher levels of consumer satisfaction (as cited in Kosiulek, 2007 In order to better implement these services, it is crucial to evaluate programs and their effectiveness. Capella & Turner (2004) pointed out that there has been traditionally a tendency to utilize quantitative measures; for example cost analysis or the percentage of the successfully closed case numbers. Due to the nature of social work, however, professionals and clients need to build a strong relationship in order to facilitate many of these processes.…”
Section: Measuring Service Satisfactionmentioning
confidence: 99%
“…In addition, Hein, Daniel & Uruk (2005) suggested that an analysis of client satisfaction in a vocational rehabilitation field is pivotal in creating client empowerment, client directed services, and selfdetermination. By reviewing client satisfaction, it is possible to improve various areas of vocational rehabilitation, such as planning, evaluating counselors and the programs, providing feedback and identifying needs for staff training (Capella & Turner, 2004).…”
Section: Measuring Service Satisfactionmentioning
confidence: 99%